Impact of chronic anthropogenic disturbance and environmental factors on natural regeneration in Caatinga dry forest - NOUTCHEU, Ronald (2022)
Natural regeneration is a complex and very important ecological process involving various factors that contribute to the recovery of tropical forest ecosystems. Understanding how these natural and human factors affect this highly disturbed biome will be a great step for its conservation and restoration. Thus, the aim of this study was to investigate the effects of chronic anthropogenic disturbances and environmental factors (aridity, soil fertility and light availability via leaf area index) on regeneration mechanisms (seed rain, soil seed bank, woody plant regenerating assemblages, and resprouts) (Chapter 1) and to assess how seedling-sized resprouts respond to experimental coppicing along disturbance and environmental gradients (Chapter 2) in a human modified landscape of Caatinga dry forest. The structure, richness, diversity and composition of regeneration mechanisms data were collected from 18 plots (20m×50m) and, while experimental coppicing from 15 plots (20m×50m) in the Catimbau National Park, Buíque, Pernambuco, Northeast Brazil. We found very low dense and impoverished regenerating assemblage, with the seed rain density ranging from 0.2 to 432.3 seeds per m2, density of viable soil seed bank varing from 5 to 2555 seeds per m2, density of true seedling ranging from 0 to 5.91 ind/ m2, true sapling density from 0 to 0.66 ind/ m2 and sprout density from 0 to 1.28 ind/ m2. Resprouting was the most important mechanism of regeneration in terms of species richness and abundance, mostly from the stem with 63% of regenerating assemblages. Abundance and species richness of regeneration mechanisms were contrasting related to CAD and environmental factors. Species composition of soil seed bank, all regenerating assemblages and resprouts were explained only by aridity. In relation to coppicing response, we observed a high resprouting capacity as all 19 species tested and around 74% of all individuals presented new shots after experimental coppicing. We found that only the number of new shoots was negatively influenced by rainfall and soil fertility. Moreover, considering the five species distributed in at least five plots across the focused gradients, negative effect of chronic disturbance, leaf area index and rainfall were observed in new shoot length, new shoot diameter and resprouting capacity indices (shoot diameter and stem diameter ratio) of Annona leptopetala and Trischidium molle, and positive effect of rainfall was observed in new shoot length, new shoot diameter and resprouting capacity indices of Cnidoscolus bahianus. These results demonstrate the negative effect of chronic anthropogenic disturbances on regenerating assemblages and show the capacity of seedling- size resprouts to persist in disturbed area. Thus, the predicted increased aridity associated to increased human disturbance in the Caatinga region can lead to unknow effects on long-term forest dynamic, biodiversity persistence and forest resilience.